2007
DOI: 10.1161/circulationaha.106.681429
|View full text |Cite
|
Sign up to set email alerts
|

Very Long-Term Survival Implications of Heart Valve Replacement With Tissue Versus Mechanical Prostheses in Adults <60 Years of Age

Abstract: Background-Several centers favor replacing a diseased native heart valve with a tissue rather than a mechanical prosthesis, even in younger adult patients. However, long-term data supporting this approach are lacking. We examined the survival implications of selecting a tissue versus a mechanical prosthesis at initial left-heart valve replacement in a cohort of adults Ͻ60 years of age who were followed for over 20 years. Methods and Results-Comorbid and procedural data were available from 6554 patients who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
125
3
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(139 citation statements)
references
References 18 publications
7
125
3
4
Order By: Relevance
“…14 Structural deterioration of bioprostheses has been documented in 10-30% of survivors at 10 years, and 30-60% at 15 years. 4-6, 22 Early failure, however, is not rare. 23 The potential for earlier failure of surgical valves is evidenced by a relatively short median time to therapy in the global VIV registry of only 9 years (IQR, 6-12 years).…”
mentioning
confidence: 99%
“…14 Structural deterioration of bioprostheses has been documented in 10-30% of survivors at 10 years, and 30-60% at 15 years. 4-6, 22 Early failure, however, is not rare. 23 The potential for earlier failure of surgical valves is evidenced by a relatively short median time to therapy in the global VIV registry of only 9 years (IQR, 6-12 years).…”
mentioning
confidence: 99%
“…However, in some recent studies; researchers found that the 20-and 25-year survival rate in patients younger than age 50 did not differ between those who received tissue or mechanical devices. The findings show that at 20 years follow-up, the overall health risk of receiving a tissue valve is not greater than that of having a mechanical valve, even in young patients However; reoperation rates were significantly higher in patients receiving both aortic and mitral tissue valves 6,7 .…”
Section: Case Reportsmentioning
confidence: 80%
“…In our patient, however, due to the aggressive and invasive nature of the Staphylococcus aureus the aortic annulus was completely destroyed and there was even evidence of an actual perforation through the leaflets. In patients less than 65 years of age mechanical valves have been shown to be much more durable with a lower incidence of primary valve failure compared to bioprosthetic valves [2], despite comparable overall mortality between the two options [3]. Reoperation rates are significantly higher for bioprosthetic valves, however longer survivals without additional surgery are expected with newer models [4].…”
Section: Discussionmentioning
confidence: 99%